Double-edged transparency in teams - BAG, Parimal (Institutional Knowledge at Singapore Management University, 2011)
In a team project with significant complementarities between various players' individual tasks, news of early success by some encourages others to push ahead with their own tasks while lack of success has the opposite effect. This ex-post disparity in incentives created gives rise to two differing implications, ex ante, for an ideal team transparency. Sometimes it is better to commit to complete secrecy within the team of the various participants' interim progress as it mitigates the negative effect of failures. In some other situations, commitment to full disclosure is better as players are then encouraged to be proactive by exerting efforts in the early rounds and motivate other team members into continued activities by way of interim progress. Transparency (of outcomes) thus has double edges -- it can boost incentives or dampen incentives.